The case for 2d turbulence in Antarctic data - Humi, M. (Societa italiana di fisica, 2003)
In this paper we analyze the data that was collected at the British Haley Station in Antarctica on June 22, 1986. This data contains measurements of the temperature and wind velocity at three heights (5 m,16 m and 32 m). Using the Karahunen-Loeve algorithm we decompose this “raw” data into mean flow, waves and turbulent residuals. We then apply three tests to find if the turbulent field might represent “two-dimensional turbulence”. The first of these tests was devised by Dewan (see Radio Sci., 20 (1985) 1301), while the second relates to the scaling of the structure function (see LindborgE., J.Fluid Mech., 388 (1999) 259). To confirm further the results of these two tests, we show that around a frequency of 0.5 rad/s most of the spectral plots for the raw data exhibit a slope of −3. We also construct a scaling model in an attempt to interpret part of the high-frequency spectrum of this data which is almost flat and discuss its possible relation to Bolgiano “buoyancy range turbulence”.